2010
DOI: 10.1007/s00394-010-0130-y
|View full text |Cite
|
Sign up to set email alerts
|

The presence of ochratoxin A in cord serum and in human milk and its correspondence with maternal dietary habits

Abstract: This study confirms that OTA is widely present in human milk and therefore could pose a risk for the newborn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 25 publications
2
43
1
Order By: Relevance
“…The result of a similar study in Egypt indicated that from a total 120 human milk samples, OTA was found in 43 (35.8%) of the samples (22). In addition, the mean concentration of the toxin in this study was higher than that of the previous studies, such as 17.5 ng/L in Brazil (12), 10-57 ng/L in Italy (23,24), and 17-30 ng/L in Germany (16), while lower amounts such 8.87 ng/L was noticed in Egypt (25), 106 ng/L in Chile (26), 39.8 ng/L in Norway (27), and 7900 ng/L in Sierra Leone (28). …”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The result of a similar study in Egypt indicated that from a total 120 human milk samples, OTA was found in 43 (35.8%) of the samples (22). In addition, the mean concentration of the toxin in this study was higher than that of the previous studies, such as 17.5 ng/L in Brazil (12), 10-57 ng/L in Italy (23,24), and 17-30 ng/L in Germany (16), while lower amounts such 8.87 ng/L was noticed in Egypt (25), 106 ng/L in Chile (26), 39.8 ng/L in Norway (27), and 7900 ng/L in Sierra Leone (28). …”
Section: Discussioncontrasting
confidence: 83%
“…For instance, Nordic Working Group has suggested the highest daily TDI of OTA level in human's body as 5 ng/kg of baby weight (30). Recently, based on the regulations made by the European Union's cooperating with European Food Safety Authority (EFSA), the tolerable weekly intake of OTA has been reported as 120 ng/kg body weight and TDI of 20 ng has been suggested for the children (23). …”
Section: Discussionmentioning
confidence: 99%
“…As a widespread food contaminant, OTA was found in human blood [26,27], milk [28], and urine [29,30,31]. This mycotoxin has several effects on animal and human health.…”
Section: Ochratoxin Amentioning
confidence: 99%
“…OTA is found to be absorbed through gastrointestinal tract and lungs of rat with high efficiency (Breitholtz-Emanuelsson, Fuchs, & Hult, 1995;Kumagai & Aibara, 1982) and shows strong binding to albumin of blood thereby ensuring the prolonged biological half-life (Scott, 2005). It is established that OTA is continuously and unavoidably being ingested with food as its detection in human plasma, serum, blood, breast milk and urine of people from many countries have been reported (Biasucci et al, 2011;Coronel et al, 2011;Coronel, Sanchis, Ramos, & Marin, 2010). Consequently, the European Union Scientific Committee for Human Feeding deemed necessary to take prudential measures in order to set a maximum permissible level of 5 mg kg À1 (5 ppb) in raw wheat, barley and rye (European Commission, 2005).…”
Section: Introductionmentioning
confidence: 98%